2011
DOI: 10.1200/jco.2011.29.18_suppl.lba1003
|View full text |Cite
|
Sign up to set email alerts
|

NCIC-CTG MA.20: An intergroup trial of regional nodal irradiation in early breast cancer.

Abstract: LBA1003 Background: Randomized trials have demonstrated that locoregional radiation after mastectomy reduces locoregional recurrence and improves overall survival (OS) in women with node positive breast cancer treated with adjuvant systemic therapy. MA.20 evaluated the addition of regional nodal irradiation (RNI) to whole breast irradiation (WBI) following breast conserving surgery (BCS). Methods: Women with high risk node-negative or node-positive breast cancer treated with BCS and adjuvant chemotherapy and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 0 publications
3
72
0
9
Order By: Relevance
“…However, little mature evidence exists regarding this issue for those patients who underwent breast-conserving surgery. Nonetheless, it is established that patients with a considerable number of positive nodes have an increased risk of regional nodal metastasis [19][20][21], and it is reported that regional nodal irradiation improves loco-regional control [20,22,23].…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little mature evidence exists regarding this issue for those patients who underwent breast-conserving surgery. Nonetheless, it is established that patients with a considerable number of positive nodes have an increased risk of regional nodal metastasis [19][20][21], and it is reported that regional nodal irradiation improves loco-regional control [20,22,23].…”
Section: Recommendationmentioning
confidence: 99%
“…The MA.20 study reported at ASCO in 2011 is one of the few RCTs investigating regional nodal irradiation for patients after breast-conserving surgery. It shows improvement of a 5-year relapse-free survival rate and overall survival after breast-conserving surgery in patients who underwent elective nodal irradiation that included internal mammary nodes [22]. However, the radiation technique was complicated by adding supraclavicular and internal mammary nodal irradiation to breast tangential irradiation, and they report an increasing incidence of radiation pneumonitis.…”
Section: Recommendationmentioning
confidence: 99%
“…Thus, several authors do not recommend prophylactic irradiation of the periclavicular fossa [17,29,30,34,48]. But according to a recent phase III study with 1,832 patients and 85% with 1-3 pN+, there was a statistically significant decrease in the rate of locoregional failure (LRF) and an increase in DFS for patients with locoregional RT [46]. Yates et al [50] found a significantly lower 10-year survival in case of supraclavicular failure, which is why PCLNI should be considered in this subset of patients.…”
Section: Periclavicular Irradiationmentioning
confidence: 99%
“…Darüber muss individuell entschieden werden [4,5,17,18]. Ergebnisse prospektiver und randomisierter Studien [MRC/EORTC (BIG 2-24) SUPREMO, EORTC-Protocol-22922-10925, EORTC-Protocol-22023-10981(AMAROS), NSABP-B32, NCIC-CTG MA.20; [16,30]] stehen derzeit noch aus.…”
Section: Radiotherapie Des Regionalen Lymphabflussesunclassified